University Selectivity, Initial Job Quality, and Longer-Run Salary - Russell Weinstein (Institute of Labor Economics (IZA), 2017)
Using Baccalaureate and Beyond data, I study whether university quality, both absolute and relative to other universities in the region, affects earnings one and ten years after graduation, controlling for the individual's SAT score. One year after graduation, high SAT score students earn 12% less if their university's regional rank is worse by 35 places, conditional on absolute university quality. This effect disappears ten years after graduation. The results suggest initial job quality does not have long-run career effects. The results also confirm the initial importance of a university's regional rank, an often overlooked dimension of university quality.
Keywords: I23; I26; J31; D83; 330; labor market return to higher education; employer learning; statistical discrimination